Produktivitas Umbi Porang (Amorphophallus oncophyllus di bawah Tegakan Jati dan Sonokeling di KPH Saradan - , PRASTUTI DEWI ARYANI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Porang (Amorphophallus oncophyllus) is one of food plants species that able to grow under annual stands and have good prospect to be developed in Indonesia. Productivity of porang tuber in each stands with different light intensity is not yet studied. This research intented to know the effect of stand species and light intensity to the productivity of porang tuber in KPH Saradan. This research used split plot design with stands species (teak and rosewood) as main plot and three different light intensity (low, medium, and high) as sub plot. Every treatment was repeated three times. Sample collection of porang tuber was done in all plots 5 m x 5 m to get wet and dry weight of porang tuber. The observation results were analyzed using 2-way anova to know the effect of stand species and light intensity to productivity of porang tuber. The results showed there were variations of porang tuber production grown under teak and rosewood stands, but at different light intensity there was no high variation. Stand species influenced to wet weight of porang tuber (F=8,64